Validity and reliability of a smartphone camera-based application for velocity-based training assessment in youth athletes - Nur Ikhwan Mohamad; Muhammad Safwan Saifullah Shamrin; Mohd Hafizuddin Baki; Chamnan Chinnasee; Wahyu Indra Bayu; Ahmad Alhussin Alali (Universitas Sriwijaya, 2026)
Research Background: This study addressed the limited evidence regarding the accuracy and consistency of smartphone-camera–based applications for monitoring barbell velocity during resistance training among youth athletes. Research Objectives: Therefore, the purpose of this study was to determine the validity and reliability of the QWIK-VBT smartphone application in measuring barbell velocity during resistance training. Method: A total of 45 youth athletes participated in this study. Barbell velocity during the deadlift exercise was measured simultaneously using the QWIK-VBT application and a linear position transducer (GymAware) as the criterion device to assess validity. Reliability was evaluated through repeated measurement trials across different sessions. Data were analyzed using correlation and reliability statistics. Results: The results showed mixed findings regarding the validity of QWIK-VBT. The application demonstrated a low and non-significant correlation with GymAware measurements (r = .252, p = .258), indicating limited concurrent validity. However, QWIK-VBT exhibited strong reliability for peak average velocity measurements, with excellent internal consistency (Cronbach’s α = .931) and a high correlation coefficient (r = .875, p < .001). Conclusion: In conclusion, although QWIK-VBT cannot yet replace gold-standard devices for precise velocity measurement, the application offers a practical and cost-effective alternative for monitoring resistance training in applied sport settings. Nevertheless, coaches and athletes should interpret the results cautiously and consider device-specific validation before consistent implementation in training programs.